Development of disease and immunity at the genital epithelium following intrarectal inoculation of male guinea pigs with Herpes simplex virus type 2 - Bourne, Nigel (Virology, 2018)
Most analyses of genital immunity to herpes simplex virus type 2 (HSV-2) have been performed in females, consequently immune protection of the male genital epithelium is incompletely understood. We developed a model of male genital HSV-2 infection resulting from intrarectal inoculation of guinea pigs. Vesicular lesions developed transiently on the perineum and foreskin concurrent with acute virus shedding. Virus shedding and recurrent genital lesions were also detected after establishment of a latent infection. Analysis of perineum and foreskin RNA detected transcripts for IFNγ, proinflammatory and regulatory cytokines, and for genes involved in migration and regulation of leukocytes. HSV-specific T cells were detected in lymphoid and genital tissues after resolution of the primary infection whereas virus-specific antibody secreting cells were detected only in lymphoid tissue. Taken together, the ability to quantify pathogenesis and local immunity in this guinea pig model represent an important advance towards understanding immunity to HSV-2 in males.